UNDERSTANDING UPI STUDENTS' PERCEPTIONS AND FINANCIAL BEHAVIORS TOWARD CRYPTOCURRENCY: A QUALITATIVE STUDY - Aziz Muradovich, Kayrdinov; Sari, Maya; Pamungkas Gautama, Budhi (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
This study explores the perceptions and financial behaviors of final-year Accounting and Management students at Universitas Pendidikan Indonesia (UPI) toward cryptocurrency. Using a qualitative approach, data were collected through semi-structured interviews with eight students. Findings reveal that while participants are aware of cryptocurrency, their understanding is often shaped by informal sources such as social media and peers, rather than academic instruction. Key themes include curiosity, emotional decision-making, peer influence, and skepticism due to volatility and lack of trust. The study highlights a significant educational gap in university curricula regarding digital finance, suggesting a need for more structured financial literacy programs. Thematic analysis further underscores the influence of behavioral finance concepts such as FOMO, loss aversion, and social proof in shaping student engagement with crypto assets.